Uji Efektivitas Antibakteri Perasan Jus Buah Nanas (Ananas comosus) Terhadap Pertumbuhan Isolat Bakteri Plak Gigi di Puskesmas Kecamatan Tanah Abang Periode April 2017 - Mitta Nurfitri Saridewi; Meiskha Bahar; Anisah Anisah (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
Dental caries or commonly known as “Tooth Decay” is one of the most common infection on human. Dental caries begins by the formation of dental plaque and it is a multifactorial disorder. One of the efforts to prevent the formation of dental caries is by utilizing plants which contain antibacterial substance. Pineapple contains bromelain, saponin, flavonoid, and tannin enzymes which functions as antibacteria. This research aimed to discover the antibacterial effectiveness of pineapple juice toward the isolate growth of dental plaque bacteria by using three different pineapple juice concentrations (25%, 50%, and 75%). The method was experimental by using dental bacteria isolate from a patient of Dental and Oral Clinic in Puskesmas Kecamatan Tanah Abang. The result shows that the higher concentration shows the bigger inhibition zone diameter formed around the plate’s paper. Consequently in concentrations of 25%, 50%, and 75%, each has its own inhibition zone rate as much as 2,90 mm (weak); 3,89 mm (weak); and 5,89 mm (moderate).